Supporting building administrator's decisions in determining maintenance costs of residential buildings. Issue 1 (2nd January 2016) - Bucoń, Robert; Tomczak, Michał
Abstract: Maintenance of multi-family buildings is a difficult and complex task, which requires a proper (multi-criteria) assessment of a building's condition as well as determining and planning maintenance costs. It requires from a building administrator to be well experienced and have skills in making decisions, which include a proper investment of limited funds allocated for maintenance. This task is usually preceded by the analysis of cost-effectiveness and validity to perform certain repairs. Taking into account the above the authors proposed a model supporting an administrator in making decisions while determining a scope of building renovation. The system algorithm proposed comprises a few stages including: building condition and its proposed repair evaluation and the choice of renovation variant. It is based on tools such as multicriteria methods to support decisions and linear programming. Calculations conducted using the suggested model allow an administrator to obtain key information for appropriate maintenance of a building, i.e. to determine a renovation variant and its cost as well as a monthly renovation contribution (at assumed number of years) to achieve assumed condition of a building.